Pemaknaan Simbol Pada Ritual Pertalekan Di Komunitas Kebudayaan Seni Silat Dan Tari Tjimande Tari Kolot Kebon Djeruk Hilir Padepokan Abah Ali Rozak Banten - Syafiqah, Nuraini; Poerana, Ana Fitriana; Kusumaningrum, Rastri (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Dharmawangsa, 2026)
This study focuses on analyzing the use of symbols in the Pertalekan Ritual of the Cultural Community of Martial Arts and Dance Tjimande Tari Kolot Kebon Djeruk Hilir (Kesti TTKKDH) at the Abah Ali Rozak Padepokan in Banten, drawing upon F.W. Dillistone’s theory of symbols. The Pertalekan ritual is a mandatory initiation tradition rich in symbolic elements, reflecting a strong sociocultural identity intertwined with Islamic values and local spirituality. Using a qualitative approach and ethnographic communication method, the study reveals that every object and action in the ritual serves not merely as a complement to the procession, but as an integral medium of communication. These symbols—both verbal and non-verbal—fundamentally affirm group identity and strengthen social cohesion within the community, ensuring the continuity of the Tjimande tradition and Islamic teachings. This is achieved by utilizing key symbolic characteristics such as figurative nature, comprehensibility, inherent power, and deep roots in society.